Encapsulación en nanoemulsiones de extractos de Equisetum arvense - Hernández Jaimes, María del Carmen (Universidad Autónoma Metropolitana, 2009)
At the moment there exists a great demand worldwide for products that are not only elaborated by its nutritional or cosmetic properties but with the purpose of to improve the health and to prevent some illnesses, for it are added compound biologically active as vitamins, minerals, dietary fiber, flavonoids, among others. The flavonoids are compoud chemical that present activity antioxidant, and they can be extracted of fruits and vegetables. A restrictive in their application is that due to the groups reagents that possess, when being extracted are degraded in a lapse of short time, losing their beneficent properties for the health, for it arises the necessity of protecting them of its degradation. For such a reason, the aim of this project was to encapsulate in nanoemulsions type o/w the extract hidrofobic of Equisetum arvense starting from the establishment of the appropriate proportions of the components; water, organic (extract in solution oils essential: ethanol) and tensoactivo as well as the determination of the area of formation of the nanoemulsion system. The compound flavonoids was extracted of Equisetum arvense (also well-known as horse line), and identified by means of cromatografy of liquids of high resolution (HPLC), for they were injected standard of quercetin and Kaempferol obtaining times of retention of 52.011±0.03 min and 60.001 ±0.02 min respectively, in the extraction four fractions were obtained; watery fraction (FA), fraction of chloroform (FC), fraction of ethyl acetate (FAE) and fraction butanolic (BFC). The obtained time of retention of each one of the fractions was compared with those obtained with the standards and those reported by Mimica and collaborators, (2008), finding similar times of retention among those reported by Mimica and collaborators, (2008), and those obtained in the laboratory. The chemical characterization of the extract of Equisetum arvense was carried out by means of quantification of total fenols, total flavonoids and activity antioxidant, with the purpose of being able to compare these results, also was carried out an extraction of Camellia sinensis (black tea) under the same conditions, obtaining that Equisetum arvense presents 0.84±0.15 mgEAG/mL of solution and Camellia sinensis 0.76±0.22 mgEAG/mL of solution finding that significant difference doesn't exist (p≤0.05) between both values. Of equal forms was found that significant difference doesn't exist (p≤0.05) between the rates of degradation of total lavonoids and activity antioxidant in the extracts of both plants. Later the fractions were taken to dryness and the obtained extract was dissolved in a solution it oils essential: ethanol (6:1). The following part of the project consisted on the formation of the nanoemulsion to protect the active compounds by means of the layer interfacial formed by the present tensoactivo in the nanoemulsion, for they were tried four tensoactivos (panodan, lactipol, tween 60 and tween 20) with the purpose of choosing the one that offered the best characteristics to the nanoemulsion, obtaining that the appropriate tensoactivo was tween 20, for what decided to use this tensoactivo to carry out the later experiments. Once elect the tensoactivo (tween 20) four formulations were designed where the dispersed phase and the phase dispersante were composed by the extract in solution oils essential: ethanol, and water respectively. these formulations stayed constant the quantity of tensoactivo, and the relationship water:organic was varied to find that with which the formation of the nanoemulsion was achieved for it was necessary to measure the drop size finding that this relationship water:organic was 16:1. Later on eight formulations were elaborated, fixing the relationship w:o and varying the tween 20 concentration (of 0.19 to 0.39 nanoemulsion g/g), obtaining the formation of the nanoemulsion between concentrations of 0.26 and 0.37 g/g nanoemulsion, to more values, a precipitate was observed, due the tween excess 20. To the nanoemulsions formed in this experiment they were determined drop size obtaining values between 19 and 23 nm, viscosity was also measured to determine the effect of the tensoactivo concentration on this, finding that when increasing the concentration of tensoactivo equal forms the viscosity increases. With the determination of the relationship water:organic which is achieved the formation of the nanoemulsion and the effect of the concentration of the tensoactivo on the drop size, the area of formation of the nanoemulsion was located in the ternary diagram of phases finding that the axis of the watery phase goes from 63 to 80%, in the axis of the Tween 20 go from 20 to 37% and in the axis of the organic, go from 0 to 17% (percentages mass). Lastly, were carried out the corresponding calculations based on the flavonoides concentration in the extract obtaining that approximately 12.7 g of nanoemulsion is equivalent to 30% (6.9 mg/day) of the daily ingest recommended for total flavonoids. The results obtained in this investigation took to conclude that the appropriate tensoactivo for the elaboration of nanoemulsions o/w low the used conditions are the monolaurato of sorbitan polioxietilen (tween 20) since it formed translucent nanoemulsions, with a drop diameter of 19 to 23 nm. The ternary diagram of phases, indicates the area of formation of the nanoemulsions containing to the extract of Equisetum arvense. The viscosity and the drop size are in function of the tensoactivo concentration.; Actualmente existe una demanda de productos funcionales, es decir, que son elaborados no sólo por sus propiedades nutricionales o cosméticas sino con la finalidad de mejorar la salud y prevenir algunas enfermedades, para ello se les agregan compuestos biológicamente activos como vitaminas, minerales, fibra dietética, flavonoides, entre otros. Los flavonoides son compuestos químicos que presentan actividad antioxidante, y pueden ser extraídos de frutas y vegetales. Una limitante en su aplicación es que debido a los grupos altamente reactivos que poseen, al ser extraídos se degradan en un lapso de tiempo corto, perdiendo sus propiedades benéficas para la salud, por lo que surge la necesidad de protegerlos de su degradación. Por tal motivo, el objetivo de este proyecto fue encapsular en nanoemulsiones tipo o/w el extracto hidrofóbico de Equisetum arvense a partir del establecimiento de las proporciones adecuadas de los componentes; agua, orgánico (extracto en solución aceite esencial : etanol) y tensoactivo así como la determinación de la zona de formación del sistema de nanoemulsión. Los compuestos flavonoides fueron extraídos de Equisetum arvense (también conocida como cola de caballo), e identificados mediante cromatografía de líquidos de alta resolución (HPLC), para ello se inyectaron estándares de quercetina y Kaempferol obteniendo tiempos de retención de 52.011±0.03 min y 60.001 ±0.02 min respectivamente, en la extracción fueron obtenidas cuatro fracciones; fracción acuosa (FA), fracción de cloroformo (FC), fracción de acetato de etilo (FAE) y fracción butanólica (FB). Los tiempo de retención obtenidos de cada una de las fracciones fueron comparados con los obtenidos con los estándares y los reportados por Mímica y col. (2008), encontrando tiempos de retención similares entre los reportados por Mímica y col, (2008) y los obtenidos en el laboratorio. La caracterización química del extracto de Equisetum arvense se llevó a cabo mediante cuantificación de fenoles totales, flavonoides totales y actividad antioxidante, con la finalidad de poder comparar estos resultados, se realizó una extracción de Camellia sinensis (té negro) bajo las mismas condiciones, obteniendo que Equisetum arvense presenta 0.84±0.15 mgEAG/mL de solución y Camellia sinensis 0.76±0.22 mgEAG/mL de solución encontrando que no existe diferencia significativa (p≤0.05) entre ambos valores. De igual forma se encontró que no existe diferencia significativa (p≤0.05) entre las tasas de degradación de flavonoides totales y actividad antioxidante en los extractos de ambas plantas. Posteriormente las fracciones se llevaron a sequedad y el extracto obtenido se disolvió en una solución aceite esencial : etanol (6:1). La siguiente parte del proyecto consistió en la formación de la nanoemulsión, para proteger los compuestos activos mediante la capa interfacial presente en la nanoemulsión formada por el tensoactivo, para ello se probaron cuatro tensoactivos (panodan, lactipol, tween 60 y tween 20) con la finalidad de elegir el que brindara las mejores características a la nanoemulsión. Obteniendo que el tensoactivo adecuado es tween 20, por lo que se utilizó dicho tensoactivo para realizar los experimentos posteriores. Una vez elegido el tensoactivo (tween 20) se diseñaron cuatro formulaciones en donde la fase dispersa y la fase dispersante estaban compuestas por el extracto en solución aceite esencial : etanol, y agua respectivamente. En estas formulaciones se mantuvo constante la cantidad de tensoactivo, y se varió la relación agua:orgánico para encontrar aquella con la cual se lograba la formación de la nanoemulsión para ello fue necesario medir el tamaño de gota encontrando que dicha relación agua:orgánico era 16:1. Posteriormente se elaboraron ocho formulaciones, fijando la relación a:o y variando la concentración de tween 20 (de 0.19 a 0.39 g/g de nanoemulsión), obteniendo la formación de la nanoemulsión entre concentraciones de 0.26 y 0.37 g/g de nanoemulsión y a valores mayores, se observó un precipitado, debido al exceso de tween 20. A las nanoemulsiones formadas en este experimento se les determinó tamaño de gota encontrándose valores entre 19 y 23 nm, además se midió viscosidad para determinar el efecto de la concentración de tensoactivo sobre ésta, encontrando que al aumentar la concentración de tensoactivo de igual forma aumenta la viscosidad. Con la determinación de la relación agua:orgánico a la cual se logra la formación de la nanoemulsión y el efecto de la concentración del tensoactivo sobre el tamaño de gota, se encontró la zona de formación de la nanoemulsión en el diagrama de fases ternario encontrando que el eje de la fase acuosa va de 63 a 80%, en el eje del Tween 20 va de 20 a 37% y en el eje del orgánico, va de 0 a 17% (porcentajes másicos). Por último, se realizaron los cálculos correspondientes en base a la concentración de flavonoides en el extracto encontrando que aproximadamente 12.7 g de nanoemulsión son equivalentes al 30% (6.9 mg/día) de la ingesta diaria recomendada para flavonoides totales. Los resultados obtenidos en esta investigación llevaron a concluir que el tensoactivo adecuado para la elaboración de nanoemulsiones o/w bajo las condiciones utilizadas es el Monolaurato de sorbitán polioxietileno (tween 20) ya que formó nanoemulsiones translúcidas, con un diámetro de gota de 23 a 19 nm. El diagrama de fases ternario, indica la zona de formación de las nanoemulsiones conteniendo al extracto de Equisetum arvense. La viscosidad y el tamaño de gota están en función de la concentración de tensoactivo.